2002
DOI: 10.1097/00004647-200209000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Real-Time RT—PCR Analysis of Inflammatory Gene Expression Associated with Ischemia—Reperfusion Brain Injury

Abstract: Ischemia-reperfusion brain injury initiates an inflammatory response involving the expression of adhesion molecules and cytokines, some of which are regulated by the nuclear transcription factor NF-kappaB. In this study the authors examined mRNA expression levels for several important genes associated with inflammation at five time points (3, 6, 12, 24, and 72 hours) after transient middle cerebral artery occlusion (MCAO) in Sprague-Dawley rats. A sensitive and quantitative technique (TaqMan real-time QRT-PCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
137
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(156 citation statements)
references
References 50 publications
18
137
1
Order By: Relevance
“…shown to protect against ischemia-induced neuronal damage (55), which is at least in part due to inflammatory and immunological reactions (56,57). In the present study, CA-074, an irreversible cathepsin Bspecific inhibitor with very low membrane permeability, completely abolished the toxicity in the conditioned medium released by activated BV2 cells.…”
Section: Discussionsupporting
confidence: 55%
“…shown to protect against ischemia-induced neuronal damage (55), which is at least in part due to inflammatory and immunological reactions (56,57). In the present study, CA-074, an irreversible cathepsin Bspecific inhibitor with very low membrane permeability, completely abolished the toxicity in the conditioned medium released by activated BV2 cells.…”
Section: Discussionsupporting
confidence: 55%
“…Regarding the size of the ischemia-induced increase in TNF mRNA expression, we in the present study observed a 58-fold increase in the level of TNF mRNA in mice with 12 hours postsurgical survival relative to unoperated control mice. This increase is larger than the 28-fold increase observed in rats at 12 hours after induction of pMCAO (Wang et al, 2001), and the 20-fold increase observed in rats 6 hours after a 2-hour episode of transient MCAO (Berti et al, 2002). The data on TNF protein is more sparse, the most thorough study being by Buttini et al (1996), who used Western blot and immunohistochemistry to demonstrate TNF from 8 hours to 1 day after induction of pMCAO in the rat.…”
Section: Discussionmentioning
confidence: 94%
“…In studies of transient MCAO in rats, TNF mRNA levels have been observed to peak at 3 hours (Wang et al, 1994) or 6 hours (Berti et al, 2002), whereas in pMCAO TNF mRNA levels were observed to peak either at 3 hours (Buttini et al, 1996), 6 hours (Kim et al, 2002), or 12 hours (Liu et al, 1994). Regarding the size of the ischemia-induced increase in TNF mRNA expression, we in the present study observed a 58-fold increase in the level of TNF mRNA in mice with 12 hours postsurgical survival relative to unoperated control mice.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory processes are known to be associated with the acute cerebral ischemic condition, including the activation of resident brain cells such as microglial cells localized within the ischemic region, and the rapid synthesis of cytokines and chemokines (Barone and Feuerstein, 1999). An increased level of pro-inflammatory cytokines is an early feature of acute brain injury induced by clinical and experimental cerebral ischemia (Berti et al, 2002;Zaremba and Losy, 2004). To investigate whether TLR4 deficiency will prevent the production of inflammatory cytokines following GCI/R, we examined IL-6, TNFα, Fas ligand and high mobility group box 1 (HMGB1) in HF tissue from TLR4 -/-and WT mice.…”
Section: Discussionmentioning
confidence: 99%